Surface treatment of electrodeposited n-type Cu2O thin films for applications in Cu2O based devices - Jayathilaka, K.M.D.C.; Kapaklis, V.; Siripala, W.; Jayanetti, J. K. D. S. (My University, 2014)
In this Letter, we report the effects of ammonium sulfide [(NH4)2S] surface treatment on electrical and optical charac teristics of the electrodeposited n-type Cu2O thin films on Ti substrates. Films characterized structurally and morphologi cally before and after the surface treatment were compared using conductivity, spectral photoresponse and current– voltage (I–V) measurements. The ammonium sulfide surface treatment time showed an impact on optical and electrical characteristics of the films. Treated Cu2O films exhibited en hanced conductivity giving rise to a 50-fold increase in the photocurrent and improved I–V characteristics. It was found that the sulfur passivation resulted in a nearly ohmic behav iour for Au or Ni contacts made with n-type Cu2O whereas Ag or Cu contacts showed nearly Schottky behaviour. The re sults showed that ammonium sulfide treatments were very effective to passivate defects and improve the optical and electrical properties of polycrystalline n-type Cu2O thin films that may provide a solid platform for Cu2O based devices of enhanced quality.
Keywords: n-type Cu2O; Thin films; Electrodeposition; Sulfur treatment; Defects; I–V characteristics; Photocurrent